2015
DOI: 10.1039/c5ra18791e
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric surface effect on the configuration of bilayer Si/SiGe nanosprings

Abstract: This study investigates the asymmetric surface effect on nanosprings composed of Si/SiGe bilayer thin films.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
(31 reference statements)
0
3
0
Order By: Relevance
“…Although in the past decade several approaches were proposed to fabricate and model helical deformations, most of them were based on the idea of building internal stresses within a multilayer structure which only exhibits a one-shot deformation to a helical shape. [24][25][26][27][28][29][30][31][32] For example, the formations of general chiral morphologies such as nanohelices in nanomaterials induced by anisotropic surface stresses have been studied. 32 Yet, these one-shot deformation approaches are not applicable for actuators and robots that require reversible and repeatable motions.…”
mentioning
confidence: 99%
“…Although in the past decade several approaches were proposed to fabricate and model helical deformations, most of them were based on the idea of building internal stresses within a multilayer structure which only exhibits a one-shot deformation to a helical shape. [24][25][26][27][28][29][30][31][32] For example, the formations of general chiral morphologies such as nanohelices in nanomaterials induced by anisotropic surface stresses have been studied. 32 Yet, these one-shot deformation approaches are not applicable for actuators and robots that require reversible and repeatable motions.…”
mentioning
confidence: 99%
“…Previous experimental studies on Si/Cr strips have confirmed that the scrolling behavior and the diameter of the rolled-up structures can depend on the layer thickness, 8 the strip width, 9, 10 the misorientation angle between the strip axis and the preferred scrolling orientation, 11 and anisotropic underetching on different Si substrates. 12 Additional surface and edge effects also play a role in strained microstructures, 13, 14 which provides additional freedom when designing 3D geometries.…”
mentioning
confidence: 99%
“…Many researchers have used continuum modeling 13, 14, 2426 and atomic modeling 2729 to study scrolling in multilayer nanostructures. Multiscale modeling approach is also available to combine both nanoscale atomic behaviors and macroscopic deformation.…”
mentioning
confidence: 99%